Effect of solidification rate on pore connectivity of aluminium foams and its consequences on mechanical properties - Lázaro, J.; Solórzano, E.; Rodríguez-Pérez, M.A.; Kennedy, Andrew R. (Elsevier, 2016)
This study evaluates the influence of solidification rate on the generation and control of pore connectivity of closed-cell aluminium foams. Additionally, it gives the experimental support to evaluate and model the effect of this pore connectivity on the mechanical properties. A collection of AlSi10 foams produced via powder metallurgy route, with porosities between 0.65 and 0.85, were examined. During production, applied heating conditions were the same in all cases but the cooling conditions were varied in order to promote different solidification rates in a wide range (from -1 to -15 K/s). Structural characterisation was performed by gas pycnometry and X- ray microtomography while the mechanical properties were evaluated by microhardness measurements and uniaxial compression tests. Results showed a clear reduction of pore connectivity when increasing the solidification rate. The consequence is a prominent improvement of the foam strength over the one expected from just the matrix refinement. Further analysis on this relationship between the pore connectivity and the mechanical properties, has allowed to propose a correction to the theoretical model for collapse strength in closed cell foams to consider such contribution and predict more accurate results.